Zarządzanie placówką medyczną – optymalizacja działań organizacyjnych na przykładzie przychodni przyszpitalnej - Jolanta Meller (Studia i Materiały)
Ongoing changes in the environment of medical institutions are the reason for their important changes in management and organizational approach of the management staff. These changes often cause a strong need to optimize organizational activities in managed entities. In this article, the issue of optimization of specific organizational processes taking place in a clinic has been researched, as exemplified by the Hospital Clinic of the Provincial Hospital named after John Paul II in Bełchatów. The article identifies the problems and presents the implementation of remedial processes